Effect of Resource-Based Learning Models on Islamic Education Learning Outcomes in Elementary Schools - Suryani, Andria; Kenedi, Gusril; Batubara, Juliana (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2025)
This study was motivated by the low learning outcomes in Islamic Religious Education at Andalas Elementary School 22, Indonesia, due to the use of conventional learning models that did not actively engage students. To overcome this, a Resource Based Learning model was implemented, utilizing various learning resources to improve student independence and learning outcomes. This study aims to determine the effect of the Resource Based Learning model on Islamic Religious Education learning outcomes in elementary schools. The type of research used is quantitative with a quasi-experimental method, involving two groups, namely experimental and control, each consisting of 20 students. The research instrument was an achievement test with a reliability of 0.947. The data were analyzed using the Kolmogorov-Smirnov Two Sample test and the t-test with the help of SPSS version 29. The results showed a significant difference between the learning outcomes of the experimental and control groups, with a significance value of 0.01 < 0.05. This proves that the Resource-Based Learning model has a positive and significant effect on improving Islamic Education learning outcomes in elementary schools. Therefore, the application of the Resource-Based Learning model can be an alternative effective and innovative learning model to improve the quality of Islamic Education learning in elementary schools through increased active participation, independence, and learning outcomes of students.